Determination of Leading Sectors in West Nusa Tenggara Province Using the Input-Output Approach - Siti Sarah NH; Sahri, Sahri; I Dewa Ketut Yudha; Najmeh Sajedianfard; Joanna Maria Kozak; Amin Osama Shammout (Tinta Emas Publisher, 2025)
The increase in added value generated by economic units based on business sectors is one of the main drivers of economic growth. High economic growth is often used as an indicator of successful economic development in a region. However, not all sectors contribute equally to this growth, making it essential to identify key sectors with strong intersectoral linkages within the economic system. This study employs a descriptive quantitative method by analyzing secondary data obtained from the Central Bureau of Statistics (BPS) of West Nusa Tenggara (NTB) for the year 2021. The analysis utilizes an input-output approach to determine priority sectors based on the Dispersion Power Index (DPI) and Sensitivity Index (SID). The Dispersion Power Index measures backward linkages, indicating the extent to which a sector stimulates other sectors through input demand. Meanwhile, the Sensitivity Index measures forward linkages, reflecting the sector’s dependence on other sectors through output sales. The findings reveal that the manufacturing industry, electricity and gas supply, and transportation and warehousing sectors exhibit high DPI and SID values, making them strategic sectors in driving NTB’s economic growth. Additionally, the agriculture, forestry, and fisheries sectors demonstrate high SID values despite having relatively lower DPI, highlighting their significant role in the regional economy. Therefore, NTB’s economic development strategy should prioritize sectors with high linkage indices while also designing policies to support sectors with lower indices to ensure balanced and sustainable economic growth.